Analysis of Indonesian Capital Market Reaction to the Inauguration of the Indonesian Cabinet in 2024 - Regita Putri Wardani; Christimulia Purnama Trimurti; Gusti Ngurah Joko Adinegara; I Wayan Ruspendi Junaedi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The inauguration of the Indonesian Cabinet is considered one of the major political events that has the potential to influence the capital market. This study aims to analyze the reaction of the Indonesian capital market to the 2024 Cabinet Inauguration event. Specifically, the research seeks to examine market conditions during the Cabinet Inauguration in 2024 and to determine whether there were any abnormal returns during this period. The study uses secondary data obtained from the Indonesia Stock Exchange (IDX), with a sample consisting of stock prices from 44 companies that remained in the LQ45 index during the period from May 22, 2025, to October 23, 2025. The research method involves abnormal return analysis and statistical testing (hypothesis testing) of abnormal returns. The results show that during the Cabinet Inauguration period, there were 110 positive abnormal returns and 154 negative abnormal returns among LQ45 stocks. This indicates that, in general, the LQ45 stocks yielded returns lower than the expected returns during the observation period. Hypothesis testing reveals that there were no statistically significant abnormal returns during the Cabinet Inauguration event in 2024. Therefore, the event did not contain information perceived as valuable for investment decision-making by investors and thus did not significantly affect abnormal returns in the Indonesian capital market.